Edge-SiamNet and Edge-TripleNet: New Deep Learning Models for Handwritten Numeral Recognition - ZHANG, Le; JIANG, Weiwei (IEICE Transactions on Information and Systems, 2020)
Handwritten numeral recognition is a classical and important task in the computer vision area. We propose two novel deep learning models for this task, which combine the edge extraction method and Siamese/Triple network structures. We evaluate the models on seven handwritten numeral datasets and the results demonstrate both the simplicity and effectiveness of our models, comparing to baseline methods.